AN ERROR ANALYSIS OF FOREIGN LANGUAGE LEARNING IN THE TERMINAL MOVIE - SUSWANTO ISMADI MEGAH (JEE (Journal of English Education), 2015)
This research aimed to analyze the errors done by the main actor of The Terminal film who came to America to learn English. The data werecollected from the dialog done by the main actor of the film. The research was qualitative design, and the result of the research showed the errorswere influenced by the first language.